Criminal Justice’s Ailing Role - Kagu, Abubakar Bukar (Advances in Social Sciences Research Journal, 2017)
The general philosophy of social contrcat is premised on the notion that the state assumes the role of maintaining social relation through diverse political ideas and strategies. Within the context of this historical arrangement, the institution of criminal justice has been foremost in shaping the relationship between members of the community by defining rights and sanctions. These socio-legal trajectories that developed through theories and policies have continued to define the various strategies of crime control as well as the jurisprudence of punishment. It has also been the key measure for the legitimacy of crime control and other dispute resolution technics (Davies et al. 2009). Being a significant component in the formation of political systems, the institution of criminal justice has also developed to encapsulate the values of democracy, constitionalism and human rights. It is from these ideas that criminal justice institutions mainly the police, the prosecutors, the courts and prisons derived their legitimacy, that are today seen by many as the ideal mechanism for maintaining social order. These agencies have, over time, gained prominence within the framework of a larger political order, engaging themselves as some “product of incremental enlightenment, benevolence, and a consensual society” (Burke 2012: 194). Despite these lofty assumptions about the role of criminal justice in the society, this paper argues that the policies and practices in criminal justice are far from benign. By bringing to discourse the contemporary realities of penal justice, this paper argues that many of the traditional values of criminal justice have been tremendously altered; conventional narratives are replaced by a new kind of penology. This includes the way in which the role and rights of various parties and participants in the system have been reconfigured as well as the economic way of thinking that is steadily disrupting the balance and objectives of the entire institution of criminal justice.